(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In the article by the application of the method of isolong an attempt was made to research the main structural features of the Earth Crust sedimentary layer for Vayk-Syunik region. For this purpose the morphostructural models of the sedimentary layer for research area were composed, which characterize its different depth horizons, and comparative analysis were made with the structural heterogeneities of the crystalline fundament surface.